Production of excited charm and charm-strange mesons at HERA - Chekanov, S; Derrick, M; Magill, S; Musgrave, B; Nicholass, D; Repond, J; Yoshida, R; Mattingly, M; Antonioli, P; Bari, G; Bellagamba, L; Boscherini, D; et al. (2009)
The production of excited charm, D 1(2420)0 and D 2* (2460)0, and charm-strange, D s1(2536)±, mesons in ep collisions was measured with the ZEUS detector at HERA using an integrated luminosity of 126 pb -1. Masses, widths and helicity parameters were determined. The measured yields were converted to the rates of c quarks hadronising as a given excited charm meson and to the ratios of the dominant D 2* (2460)0 and D s1(2536) ± branching fractions. A search for the radially excited charm meson, D *(2640)±, was also performed. The results are compared with those measured previously and with theoretical expectations. © 2009 Springer-Verlag / Società Italiana di Fisica.